Estudio de adición de crioprotectores en caracterización físico-química del liofilizado de emulsión de PFOB (2017)
"Perfluorocarbon compounds have been investigated as possible blood substitutes because of their ability to transport and dissolve respiratory gases. Perfluorooctylbromide (PFOB) is a PFC that must be emulsified for intravenous application. However, the emulsion presents physical and chemical instability when stored for long periods of time, thus affecting the final quality of the product. Freeze-drying of the emulsion is carried out with the aim of increasing the shelf life and stability of the emulsion, being a field of interest in pharmaceutical applications. However, during lyophilization process tension and stress are produced in freezing and drying stages which destabilize the emulsion. In order to avoid colloidal instability of the system and possible leaks of PFOB in lyophilization, the implications of adding cryoprotectant agents before lyophilization and their implication in the characteristics of the reconstituted were evaluated over time." -- Tomado del Formato de Documento de Grado.